An Analysis of Interlanguage Performed by Students of an Islamic Boarding School in Tasikmalaya - feisal aziez (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2016)
This descriptive study aims at: (1) finding out and describe the phonological,lexical, and syntactic forms of English language learners’ inter language, and (2)finding out whether there are any differences in the inter language of the learners ofdifferent grades. The subjects of this research were 24 learners of the first, second,and third grade of an Islamic boarding school in Tasikmalaya. The data werecollected from students’ conversations, interviews, and reading aloud. The datawere recorded and transcribed. Then, the data were filtered by using Corder’sprocedure. The results of the research reveal the existence of the following aspectsin the learners’ inter language: (1) phonological transfers, (2) lexical transfers, (3)syntactic transfers, (4) phonological overgeneralizations, (5) lexicalovergeneralizations, and (6) syntactic overgeneralizations. This research also foundout some differences in the inter language of the students of different grades.